Analisis Regresi Komponen Utama untuk Mengatasi Multikolinearitas pada Faktor-Faktor yang Mempengaruhi Indeks Pembangunan Manusia - Hidayatullah, Azka Fariz; Saputra, Dede; Inarah, Filzah; Evita, Isma; Fadillah, Muhammad; Harsyiah, Lisa (JSN : Jurnal Sains Natural, 2024)
West Nusa Tenggara and East Nusa Tenggara provinces are among the provinces with low human development indexes. There are seven factors used in this study that are considered to affect the human development index in the two provinces, namely gross regional domestic product, poor population, open unemployment rate, population, life expectancy, labor force and average years of schooling. The method used by researchers in overcoming multicollinearity in this study is principal component regression. Therefore, this study aims to apply principal component regression in overcoming the problem of multicollinearity on the the effect of gross regional domestic product, poor population, open unemployment rate, population, life expectancy, labor force and average years of schooling on the human development index. Based on the results of the analysis that has been carried out, the principle component regression model is obtained as follows Y = 42.548 + 0.00000991X_1 + 0.0371X_2 + 0.343X_3 + 0.000005949X_4 + 0.2532 + 0.000012947X_6 + 0.1348X_7. With the coefficient of determination (R^2) 0.834.